Cortical adaptation and frequency selectivity: from single neurons to evoked potentials - Woolnough, Oscar (2017)
Adaptation is a reduction in a neural response to a sensory stimulus resulting from repeated presentation of the stimulus and is an important aspect of sensory neural coding. This phenomenon is sensitive to changes in parameters of the repeating stimuli and the adaptation will be greatest when the stimuli are identical and diminish with changes in stimulus parameters between repetitions. In the auditory system it has been shown the specificity of cortical adaptation relates primarily to the frequency of a stimulus, with wider frequency separations between sequentially presented stimuli resulting in a reduced level of adaptation. This frequency specific adaptation has been measured at multiple scales, in EEG recordings in humans and at the single unit level in animals but the results from each implicate different underlying neural mechanisms. This thesis attempts to elucidate some of those differences by investigating the effects of the differences in methodology between the studies, the inter-species differences in adaptation characteristics and the effects of anaesthesia on sensory neural processing. This touches upon the forward and inverse modelling problems in computational neuroscience and also the issues with relating results from EEG in awake humans with single neuron recordings in anaesthetised animals. The thesis starts by building on previous work looking at whether the frequency selectivity of adaptation can be changed by the temporal properties of the adapting stimuli. It was found that a sharpening of frequency selectivity of adaptation could be induced by using multiple repeated adapters but not with single onset, prolonged duration adapters. This repetition induced sharpening was also shown to act independently of attention despite there being an attentionally induced sharpening effect on adaptation. This EEG adaptation tuning was explained by an extension of a computational model previously proposed to explain stimulus specific adaptation and oddball responses in single neurons. The model was a two-layer network with independently adapting synapses and is able to quantitatively reproduce the observed non-monotonic adaptation and sharpening of tuning observed in our EEG responses, and the effects of repeated and prolonged adapters. To further investigate this then this study was replicated in an anaesthetised animal model with recordings directly from auditory cortex. This study showed none of the repetition induced sharpening effects and dramatically quantitatively different adaptation results compared to the human studies. To help explain these results then recordings were made in awake guinea pigs with chronically implanted intracranial EEG electrodes and invasive depth electrodes to discover whether these differences were a result of species or anaesthesia. These experiments start to explain some of the discrepancies seen before, with adaptation time constants orders of magnitude different to those in humans and differences in their innate frequency selectivity. Alongside this then the effects of anaesthesia on the results were investigated under a range of anaesthetic regimes including opiates, NMDA antagonists and GABA potentiators. It was shown that anaesthetic choice has substantial effects on sensory signalling, temporal processing and cross-modal interactions which result in multifaceted effects on the characteristics of adaptation. This thesis builds on previous work on the plasticity of frequency selectivity of adaptation in auditory cortex and helps to characterise this phenomenon and explain its mechanisms. This work also highlights the difficulties of directly relating studies and findings between humans and animal studies of the auditory system, demonstrating the magnitude of difference in temporal and frequency processing between species and also shows the substantial changes in sensory processing induced by anaesthesia and modulated by anaesthetic choice.